Influence of the bone graft materials used for guided bone regeneration on subsequent peri-implant inflammation: an experimental ligature-induced peri-implantitis model in Beagle dogs - Ryo Sato; Takanori Matsuura; Tatsuya Akizuki; Shunsuke Fukuba; Munehiro Okada; Kohei Nohara; Shunsuke Takeuchi; Shu Hoshi; Wataru Ono; Kiichi Maruyama; Yuichi Izumi; Takanori Iwata (SpringerOpen, 2022)
Abstract Purpose We aimed to histologically evaluate the influence of bone materials used during guided bone regeneration (GBR) on subsequent peri-implantitis in an experimental ligature-induced peri-implantitis model in beagle dogs. Methods Bilateral mandibular premolars (PM2-4) were extracted from six beagle dogs. After 3 months, standardized bone defects (3 mm [mesio-distal width] × 2 mm [bucco-lingual width] × 3 mm [depth]) were created in the experimental group, with simultaneous dental implant placement at the center of the defects. The defects were randomly filled with either autograft (AG) or deproteinized bovine bone mineral (DBBM) and covered with a collagen membrane. In the control group, implant fixtures were placed without creating an intrabony defect. After 3 months, a healing abutment was placed. Four weeks later, a 3-0 silk thread was ligated around the implants to induce peri-implantitis. After 4 weeks, the specimens were dissected and histologically examined. Results There were no clinical findings of inflammation until silk thread ligation. Four weeks after the onset of peri-implantitis, gingival redness and swelling were seen with mild resorption of the peri-implant bone on dental radiographs. There were no significant differences between the AG, DBBM, and control groups for the following parameters: bone-to-implant contact, distance from the implant shoulder to the base of the bone defect, area of bone defect, and area of new bone. Conclusions Within the limitations of this study, it can be concluded that peri-implant tissues after GBR using AG and DBBM underwent the same degree of bone resorption by peri-implantitis as the no defect group.